2011
DOI: 10.1089/jwh.2010.2517
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain and Daughter's Age at Menarche

Abstract: Background: Sexual development begins in utero and enters a dormant phase during infancy. The influence of maternal gestational weight gain (GWG) on daughter's age at menarche has not been explored. Methods: We investigated the association between maternal GWG and age at menarche (< 11 years, 11-15 years, > 15 years of age) in a large cohort study of U.S. nurses, The Nurses' Health Study II (NHS II), and the Nurses' Mothers' Cohort Study. Results: Among 32,218 respondents, 7% reported age at menarche < l1, 90%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 63 publications
5
37
0
Order By: Relevance
“…Recent studies [3740] provided evidence for relationships between some anamnestic and clinical traits of mothers and AAM of their daughters. However, some controversy still exists [37, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies [3740] provided evidence for relationships between some anamnestic and clinical traits of mothers and AAM of their daughters. However, some controversy still exists [37, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Factors that are likely to lie on the causal path (birth weight, gestational age, maternal postpartum obesity and change in postpartum weight) were not considered potential confounders. 31 We performed a sensitivity analysis by including pubertal status of the offspring as a potential confounder because it may or may not 32 lie on the causal path. Our goal was to fit a parsimonious regression model and remove potential confounders if their inclusion did not satisfy our a priori change-in-estimate criterion (≥10% change in the risk ratio).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the existing literature, we selected the following confounders: socioeconomic status (SES), mothers’ race/ethnicity, mother's parity, maternal smoking during pregnancy (yes/no during 12 months before birth of child), maternal age at menarche, and breastfeeding (yes/no) (2, 34, 35, 46-49). For SES, we included the log parental income (reported at child's birth) and maternal education level (at age 25).…”
Section: Methodsmentioning
confidence: 99%
“…(34) In 2011, data from daughters whose mothers participated in the original Nurses’ Health Study (1946-1965) showed that maternal gestational weight gain (GWG) was associated with daughters’ age at menarche in a U-shaped pattern, such that excessively high (>40lbs) and low (<10lbs) GWG were associated with earlier menarche (35). However, given the homogeneity in that sample (95% non-Hispanic white), it was not possible to assess whether these associations held for other racial/ethnic groups.…”
mentioning
confidence: 99%